Executive Compensation for Top-Ranked Private Universities in the United States: A Study of a 2-Decade Change - K. Ponton, Michael (International Research in Education, 2023)
The increasing cost of attending higher education institutions in the United States of America warrants investigations into potential causal factors. As one major recurring expenditure is employee compensation, the purpose of this study was to determine if total executive compensation as a percentage of total institutional expenses has changed over the 2-decade period of 2001 to 2021 with a specific focus on the top 20 private universities in the United States that are not part of the Ivy League. Due to their excellence, these 20 institutions hold national and international attention and serve as influential models to other higher education institutions thus making them important for analysis. For these institutions, the findings suggest that total executive compensation represented an increasing percentage of total institutional expenses over this 2-decade period; however, chief executive officer base compensation represented a decreasing percentage of total executive compensation over this same period.